Manifestations, Factors of Actualization and Theoretical Explanations of Academic Inequality - Chikishev, Nikita (Visnyk of V. N. Karazin Kharkiv National University. Series Sociological studies of contemporary society: methodology, theory, methods, 2019)
The article deals with the study of academic inequality in the context of globalization. The prerequisites for the appearance of modern forms of inequality in education and science are considered. The aspect of the declarativity of official educational discourse is analyzed. It is reflected in the contradiction between articulated priorities and reality. In addition, it is noted that the official educational discourse is inherent in an apologetic reflection of the topics of rankings, which is displayed in attempts to naturalize them. The heuristic potential of the world-system approach is characterized in the framework of the study of the problems of academic capitalism. An analysis of the key concepts of the concepts of F. Braudel, I. Wallerstein and A. G. Frank is carried out, and a substantiation of their applicability for studying the relations of inequality in the sphere of education is given. The main theoretical concepts of "uneven" development of territories are considered, a comparative analysis of concepts is carried out and the author's scheme based on the synthesis of concepts of the world of system analysis and capital analysis by P. Bourdieu is proposed. The author's definitions of the concepts “academic inequality”, “construction of inequalities” and “academic capitalism” are provided. The role of university rankings in the processes of constructing academic inequality is analyzed. The interrelation of the commodification processes in education and science with globalization processes is grounded. The specific features of constructing academic inequality in modern conditions are revealed. The conclusion about the dual structure of academic inequality is formulated. Further prospects for the development of the topic in the context of studying the transformation of the institute of education are indicated.